The Burden of COPD with Type 2 Inflammation in North-West Continental Europe - Sandelowsky, Hanna; Løkke, Anders; Kocks, Janwillem; Grøttum, Helle; Bakke, Per; Vasankari, Tuula (Dove Medical Press, 2026)
Chronic obstructive pulmonary disease (COPD) is a complex and heterogeneous disease that places a huge burden on patients, health systems and societies. Yet despite this, COPD is often neglected: it is frequently underdiagnosed or misdiagnosed, and since tobacco exposure is a primary risk factor for its development, patients are often stigmatized and marginalized because they are perceived as having a “self-inflicted” disease. COPD is primarily understood to be a functional disorder with chronic airway obstruction, yet there are several underlying inflammatory pathways. For most patients with COPD, type 1 (neutrophilic) inflammation is the main such pathway; however, a considerable proportion has type 2 inflammation (associated with elevated eosinophil numbers). COPD with type 2 inflammation may represent a distinct COPD phenotype and a “treatable trait”. In fact, the response to inhaled corticosteroids (ICS) is linked to blood eosinophil levels: treatment effects begin to increase in patients with blood eosinophil counts ≥ 100 cells/μL, and most treatment guidelines recommend considering ICS for patients with blood eosinophil counts ≥ 300 cells/μL. Data on the burden of COPD with type 2 inflammation are limited. COPD with type 2 inflammation may associate with poor outcomes, and higher blood eosinophil counts positively associate with an increased risk of moderate or severe exacerbations. Exacerbations are among the most dangerous aspects of COPD, accelerating disease progression and increasing morbidity and mortality. This review explores the burden of COPD – specifically eosinophilic COPD – across north-western Europe. It aims to provide information relevant to patients, clinicians and policymakers, educating them about type 2 inflammation and its contribution to the disease burden. It has been informed by multiple stakeholders, including patients, and offers practical and achievable recommendations for enhancing the care of all patients with COPD through a better understanding of COPD with type 2 inflammation.